Virtual Reality Aggression Prevention Training for People with Mild Intellectual Disabilities : A Feasibility Study - Geraets, Chris N.W.; Dolfijn, Roelof; Robbemond, Lisanne M.; Scholte, Albert; Klein Tuente, Stéphanie; Veling, Wim (Journal of Mental Health Research in Intellectual Disabilities, 2024)
Introduction: Problems with adequately regulating aggression are comon in people with mild to borderline intellectual disabilities (MBID). Learning through experience has been shown to be effective in MBID. Therefore, we adapted an aggression prevention training that uses virtual reality (VR), which was initially made for a forensic psychiatric population. We aimed to assess the feasibility of this VR aggression training for MBID. Methods: Nine people with MBID attended the 12-session VR aggression training. Both quantitative (on session satisfaction, well-being and observed aggression), and qualitative measures (feasibility workbook evaluations and focus groups with participants and therapists) were obtained. Results: Six participants completed all sessions, and three participants dropped out because of a lack of motivation. Session satisfaction scores were high. Thematic analyses identified that participants learned coping strategies, and gained insights into emotions and triggers. Suggestions for improvement of the training included more personalization, practicing longer in VR, and more involvement of the social network in training sessions. Aggression observation measures were not feasible and no reliable results could be obtained. Conclusion: Although the dropout was substantial, the training seems feasible and acceptable for participants and therapists. However, improvements should be made to the intervention to increase efficacy, and enable better fits with participants’ specific needs.
Publisher Copyright: © 2023 The Author(s). Published with license by Taylor & Francis Group, LLC.
Keywords: aggression; anger; behavioral training; intellectual disability; Virtual reality